Biochemical and Molecular-Genetic Characterization of SFD1’s Involvement in Lipid Metabolism and Defense Signaling - Lorenc-Kukula, Katarzyna; Chaturvedi, Ratnesh; Roth, Mary; Welti, Ruth; Shah, Jyoti (Frontiers in Plant Science, 2012)
The Arabidopsis thaliana SFD1 (suppressor of fatty acid desaturase deficiency1) gene (also known as GLY1) is required for accumulation of 34:6 (i.e., 18:3–16:3) monogalactosyldiacylglycerol (MGDG) and for the activation of systemic acquired resistance (SAR), an inducible defense mechanism that confers resistance against a broad spectrum of pathogens. SFD1, which has been suggested to be involved in lipid-based signaling in SAR, contains a putative chloroplast transit peptide and has glycerol-3-phosphate synthesizing dihydroxyacetone phosphate (DHAP) reductase (also referred as glycerol-3-phosphate dehydrogenase) activity. The goals of this study were to determine if the DHAP reductase activity and chloroplast localization are required for SFD1’s involvement in galactolipid metabolism and SAR signaling. The crystal structure of a Leishmania mexicana glycerol-3-phosphate dehydrogenase was used to model SFD1 structure and identify Lys194, Lys279, and Asp332 as potential catalytic site residues in SFD1. Mutational analysis of SFD1 confirmed that Lys194, Lys279, and Asp332 are critical for SFD1’s DHAP reductase activity, and its involvement in SAR. SFD1 proteins with these residues individually substituted by Ala lacked DHAP reductase activity and were unable to complement the SAR defect of the sfd1 mutant. The SFD1–Ala279 protein was also unable to restore 34:6-MGDG content when expressed in the sfd1 mutant. In vivo imaging of a green fluorescent protein-tagged SFD1 protein demonstrated that SFD1 is targeted to the chloroplast. The N-terminal 43 amino acids, which are required for proper targeting of SFD1 to the chloroplast, are also required for SFD1’s function in lipid metabolism and SAR. Taken together, these results demonstrate that SFD1’s DHAP reductase activity is required in the chloroplast for lipid metabolism and defense signaling.